Tidal Characteristics for Disaster Preparedness in the Port Area (Case Study: Port of Semarang, Central Java) - Nurkhalis Rahili; Buddin Al Hakim; Danang Ariyanto; Eny Cholishoh; Aprijanto Aprijanto; Destianingrum Ratna Prabawardani; Tjahjono Prijambodo; Gugum Gumbira (Marine Science Department Diponegoro University, 2023)
Tanjung Emas Port, Semarang, is vulnerable to hydrometeorological disasters and tidal flooding due to tides and rising sea levels. The tidal flood also impacts human activities and industrial operations around the coastal area. Several measures have been taken to make the community resilient to tidal flooding and adapt to this disaster. A tidal flood happened in Semarang from May to June 2022 with a flood height of up to 210 cm. This incident disturbed the primary port operations, with more than 75% of the port area full of water. The total loss was estimated up to IDR 615 billion. Many factors influenced this incident, such as the rising sea levels due to global warming, tides, and other atmospheric conditions, causing weather anomalies. This study aims to compare and validate Geospatial Information Agency (BIG) tide data with Meteorological, Climatological, and Geophysical Agency (BMKG) tide data using three kinds of statistical test, that are mean relative error (MRE), root mean square error (RMSE), and mean absolute error (MAE). Also, to conduct tidal analysis using 11 years of tide data measurement to know the tide's characteristics in Semarang's coastal area. The result will be used to provide input for strategic steps and preparation for disaster preparedness that will occur in the near future. Tide data analysis using MIKE21, the IOS method. The result shows data comparison error < 5% and a Formzahl value of 1.797 with the type of tide mixture prevailing diurnal and the change of water level up to 10 cm.y-1.